2018
DOI: 10.1111/aogs.13462
|View full text |Cite
|
Sign up to set email alerts
|

RMI and ROMA are equally effective in discriminating between benign and malignant gynecological tumors: A prospective population‐based study

Abstract: We could not confirm that ROMA had diagnostic superiority over RMI in categorizing women with a pelvic mass into low-risk or high-risk groups for malignancy in a Swedish population. We have defined cut-off values for HE4 and ROMA. The lack of correlation between serum and urine HE4 obviates the introduction of urine HE4 analysis in clinical diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In the cohort of 33 patients with recorded values of both pre-and postoperative tumor markers the median levels of HE4 significantly decreased to well under upper reference limit (URL) in the group in which complete debulking was achieved (n = 28) compared to the group (n = 5) left with minimal or bulky disease (P<0.001, Fig.1A-B). In the present study, we have used 82 pmol/L as the URL in accordance with conclusions from our previous study [12]. The four patients left with bulky disease had postoperative HE4 values, which were well above the URL.…”
Section: Levels Of He4 and Ca125mentioning
confidence: 78%
“…In the cohort of 33 patients with recorded values of both pre-and postoperative tumor markers the median levels of HE4 significantly decreased to well under upper reference limit (URL) in the group in which complete debulking was achieved (n = 28) compared to the group (n = 5) left with minimal or bulky disease (P<0.001, Fig.1A-B). In the present study, we have used 82 pmol/L as the URL in accordance with conclusions from our previous study [12]. The four patients left with bulky disease had postoperative HE4 values, which were well above the URL.…”
Section: Levels Of He4 and Ca125mentioning
confidence: 78%
“…1A-B). In the present study, we have used 82 pmol/L as the URL in accordance with conclusions from our previous study [12]. The four patients left with bulky disease had postoperative HE4 values, which were well above the URL.…”
Section: Levels Of He4 and Ca125mentioning
confidence: 78%
“…When the studies conducted in the literature about the use of combined tests are examined, it is observed that there are different results Jacobs et al [10] reported the sensitivity of RMI as 85% and specificity as 97% in a study involving 101 benign and 42 malignant ovarian tumors. In another study conducted by Liest et al [11], it was shown that ROMA and RMI tests did not have superiority over each other in the preoperative malignant-benign differentiation of the adnexal mass of 784 patients. While in another study conducted on 457 patients with an adnexal mass, the ROMA test was superior to RMI (sensitivity 89% vs. 80.7%) [12].…”
Section: Discussionmentioning
confidence: 92%